Prevention and Control of Hypertension through Tera Gymnastics with Guntung Paikat Residents of Banjarbaru - Kamilia Quamila Andriani; Anisa Sujarwati; Halimatus Mayda Zahra; Muhammad Azmiyannoor; Muhammad Irwan Setiawan (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
World Health Organization estimates that in 2019 the global prevalence of hypertension is 22%. Based on the 2018 Riskesdas report, the prevalence of hypertension in Indonesia is 34.11% and South Kalimantan ranked first (44.13%). One of the risk factors for hypertension is a sedentary lifestyle. Therefore, it is necessary to empower the community related to lifestyles that affect the occurrence of hypertension. A total of 15 residents of RT.007 RW.005 in Guntung Paikat have participated in exercise to control blood pressure. Seven of them received leaflets to increase knowledge and attitudes related to hypertension. Based on the evaluation results, there was a decrease in the mean systolic (p-value=0.020) and diastolic (p-value=0.011) blood pressure between before and after exercise. The increase in mean knowledge (p-value=0.655) and attitude (p-value=0.436) was not significantly affected by the provision of leaflets.